Simultaneity in binary outcome models with an application to employment for couples - Bo E. Honoré; Luojia Hu; Ekaterini Kyriazidou; Martin Weidner (Federal Reserve Bank of Chicago, 2022)
Two of Peter Schmidt's many contributions to econometrics have been to introduce a simultaneous logit model for bivariate binary outcomes and to study estimation of dynamic linear fixed effects panel data models using short panels. In this paper, we study a dynamic panel data version of the bivariate model introduced in Schmidt and Strauss (1975) that allows for lagged dependent variables and fixed effects as in Ahn and Schmidt (1995). We combine a conditional likelihood approach with a method of moments approach to obtain an estimation strategy for the resulting model. We apply this estimation strategy to a simple model for the intra-household relationship in employment. Our main conclusion is that the within-household "correlation" in employment differs significantly by the ethnicity composition of the couple even after one allows for unobserved household specific heterogeneity.
Keywords: C01; C33; C35; E24; 330; Simultaneity; Binary Response; Fixed Effects; Moment Conditions; Employment